Placental mesenchymal stem cells suppress inflammation and promote M2-like macrophage polarization through the IL-10/STAT3/NLRP3 axis in acute lung injury - Nie, Zhihao; Fan, Qinglu; Jiang, Wanli; Wei, Shujian; Luo, Renwei; Hu, Haifeng; Liu, Gaoli; Lei, Yufei; Xie, Songping (Frontiers in Immunology, 2024)
IntroductionAcute lung injury (ALI) is a clinically severe respiratory disorder that currently lacks specific and effective pharmacotherapy. The imbalance of M1/M2 macrophage polarization is pivotal in the initiation and progression of ALI. Shifting macrophage polarization from the proinflammatory M1 phenotype to the anti-inflammatory M2 phenotype could be a potential therapeutic strategy. The intratracheal administration of placental mesenchymal stem cells (pMSCs) has emerged as a novel and effective treatment for ALI. This study aimed to investigate the role and downstream mechanisms of pMSCs in reprogramming macrophage polarization to exert anti-inflammatory effects in ALI.MethodsThe study used lipopolysaccharide (LPS) to induce inflammation in both cell and rat models of ALI. Intratracheal administration of pMSCs was tested as a therapeutic intervention. An expression dataset for MSCs cultured with LPS-treated macrophages was collected from the Gene Expression Omnibus database to predict downstream regulatory mechanisms. Experimental validation was conducted through in vitro and in vivo assays to assess pMSCs effects on macrophage polarization and inflammation.ResultsBoth in vitro and in vivo experiments validated that pMSCs promoted M2 macrophage polarization and reduced the release of inflammatory factors. Further analyses revealed that pMSCs activated the signal transducer and activator of transcription (STAT)3 signaling pathway by secreting interleukin (IL)-10, leading to increased STAT3 phosphorylation and nuclear translocation. This activation inhibited NLRP3 inflammasome activation, promoting M2 macrophage polarization and suppressing the inflammatory response.ConclusionThe study concluded that pMSCs alleviated lung injury in an LPS-induced ALI model by inhibiting M1 macrophage polarization and proinflammatory factor secretion, while promoting M2 macrophage polarization. This effect was mediated via the IL-10/STAT3/NLRP3 axis, presenting a novel therapeutic pathway for ALI treatment.